2019
DOI: 10.3390/met9060642
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Inclusions in Solid GCr15 Bearing Steels During Heat Treatment

Abstract: Laboratory heating experiments with a varied holding time of GCr15 bearing steels at 1498 K were performed to study the transformation of inclusions in solid GCr15 bearing steels during high temperature diffusion processes. Heating experiments at 1573 and 1648 K were also carried out to study the effect of these heating temperatures. Experimental results showed that inclusions transformed from Al2O3-CaO-(MgO) to Al2O3-CaS-(MgO-CaO) when the heat treatment was in the range of 1498 to 1648 K due to reactions bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…As the fatigue life of bearing steels was inversely proportional to the square root of the projected area of inclusions in high strength steels along the plane of principal shear stress, [ 31 ] the cross section of forged steels was selected for the inclusion analysis, and the chemical composition of oxide inclusions in the steel is shown in Figure 10 . According to previous research results, [ 3,32 ] Al 2 O 3 –CaO inclusions in molten steel were fully or partially transformed into Al 2 O 3 –CaS inclusions during the cooling of billets and heating process, which led to the main chemical composition of inclusions in both no. 1 and no.…”
Section: Variation Of Inclusions In Solid Steels and Rcf Test Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…As the fatigue life of bearing steels was inversely proportional to the square root of the projected area of inclusions in high strength steels along the plane of principal shear stress, [ 31 ] the cross section of forged steels was selected for the inclusion analysis, and the chemical composition of oxide inclusions in the steel is shown in Figure 10 . According to previous research results, [ 3,32 ] Al 2 O 3 –CaO inclusions in molten steel were fully or partially transformed into Al 2 O 3 –CaS inclusions during the cooling of billets and heating process, which led to the main chemical composition of inclusions in both no. 1 and no.…”
Section: Variation Of Inclusions In Solid Steels and Rcf Test Resultsmentioning
confidence: 85%
“…As the fatigue life of bearing steels was inversely proportional to the square root of the projected area of inclusions in high strength steels along the plane of principal shear stress, [31] the cross section of forged steels was selected for the inclusion analysis, and the chemical composition of oxide inclusions in the steel is shown in Figure 10. According to previous research results, [3,32] When the SEV method was used to estimate the characteristic size of inclusions, inclusions with equivalent circle diameter greater than 3 μm in each group of 24 samples were statistically analyzed. The sampling position of the inclusion scanning sample was at 1/2 radius of the cross-sectional position of the forged steel.…”
Section: Variation Of Inclusions In Solid Steels and Rcf Test Resultsmentioning
confidence: 99%
“…All originally and additionally heat-treated samples were machined from the same (single) forged structural component. Moreover, observable changes in the number and the size of inclusions in steels usually start only at annealing temperatures higher than 1250 K (e.g., [ 28 ]), which were not reached during the additional heat treatment. However, recent observations ([ 29 ]) indicated that repeated annealing, quenching, and tempering can significantly reduce both the size and the number of inclusions.…”
Section: Material Heat Treatment and Microstructurementioning
confidence: 99%
“…[ 10,11 ] Inclusions of CaO–Al 2 O 3 –(MgO) transformed into Al 2 O 3 –CaS–(MgO) during the heat treatment of solid Al‐killed steels, such as linepipe steels [ 12 ] and bearing steels. [ 13 ] For Ti‐bearing steels, the precipitation of TiN was found and in situ observed. [ 14,15 ] Inclusions of Al 2 O 3 –CaO–CaS transformed into TiN–Al 2 O 3 –CaO–CaS in shipbuilding steels.…”
Section: Introductionmentioning
confidence: 99%